2017
DOI: 10.1017/s0890060417000543
|View full text |Cite
|
Sign up to set email alerts
|

Comparing function structures and pruned function structures for market price prediction: An approach to benchmarking representation inferencing value

Abstract: Benchmarking function modeling and representation approaches requires a direct comparison, including the inferencing support by the different approaches. To this end, this paper explores the value of a representation by comparing the ability of a representation to support reasoning based on varying amounts of information stored in the representational components of a function structure: vocabulary, grammar, and topology. This is done by classifying the previously developed functional pruning rules into vocabul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…The primary goal of this experiment is to compare the predictive capability of ANNs to that of fourthyear mechanical engineering undergraduate students. In this case, function structure models are to be used to predict market values of household products (Gill et al, 2017;Mathieson et al, 2011;Sridhar et al, 2016b). Function structure models for fifteen household products were collected from the design repository (https://design.engr.oregonstate.edu/repo) and associated costs for these products were calculated as an average of five different quotes (Mathieson et al, 2011;Sri Ram Mohinder et al, 2017).…”
Section: Experiments Designmentioning
confidence: 99%
“…The primary goal of this experiment is to compare the predictive capability of ANNs to that of fourthyear mechanical engineering undergraduate students. In this case, function structure models are to be used to predict market values of household products (Gill et al, 2017;Mathieson et al, 2011;Sridhar et al, 2016b). Function structure models for fifteen household products were collected from the design repository (https://design.engr.oregonstate.edu/repo) and associated costs for these products were calculated as an average of five different quotes (Mathieson et al, 2011;Sri Ram Mohinder et al, 2017).…”
Section: Experiments Designmentioning
confidence: 99%
“…Colombo et al (2020Colombo et al ( ) 2017 Value is how beneficial something is perceived to be. Gill, Summers, andTurner (2017) 2017 Value for organisations and products can be grounded in economic theory.…”
Section: Datementioning
confidence: 99%
“…Miles (1972Miles ( ) 1966 Value is the relationship of product worth to product cost. Miles (1966) Desbarats 2006; Gill, Summers, and Turner 2017;Grace et al 2015;Hamilton 1996) refers to the metrics of market share, innovation, differentiation, or a result superior to that of the competition. From the value interpretations given in Table 1, it can be concluded that value as an outcome in return for an input (e.g.…”
Section: Chase (2001)mentioning
confidence: 99%
“…Function model characteristics modelling: In order to investigate the effect of the ability of different functional structure models to support decision-making Gill et al (2017) modelled the relation between the complexity metrics of a functional models (e.g. number of elements or shortest paths between the inputs and outputs of the model) with respect to the market value using neural networks.…”
Section: Function Modellingmentioning
confidence: 99%